Pengaruh Kecerdasan Emosional dan Kecerdasan Intelektual terhadap Kinerja Karyawan di PT. Bank Negara Indonesia Kantor Cabang Bengkalis pada Mada Pandemi COVID-19 - Amelia, Dea; Razak Jer, Abd. (Seminar Nasional Riset Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of emotional intelligence and intellectual intelligence on employee performance at PT. Bank Negara Indonesia Bengkalis Branch Office. The population in this study were all employees of PT. Bank Negara Indonesia Bengkalis Branch Office totaled 31 people. The sampling method used in this study is the saturated sample method, that is, all of the population is sampled. Data analysis in this study used multiple linear analysis. The results showed that partially emotional intelligence had a positive and significant effect on employee performance and intellectual intelligence had a positive and significant effect on employee performance. Meanwhile, simultaneously emotional intelligence and intellectual intelligence have a positive and significant effect on employee performance.